Analysis of Influencing Factors Income of Corn Farmers (Zea mays L.) (Case Study in North Tolo Village, Kelara District, Jeneponto Regency) - Huzair Syahran (Central Research Institute For Agriculture, 2022)
This study aims to determine the factors that affect farmers' income in the study area. This research was conducted in Keluruhan Utara Tolo, Kecamatan Kelara, Kabupaten Jeneponto from August to September 2012. The aim of the study was to determine the factors that affect the income of corn farmers and to find out how much the average income level is. The first proposed hypothesis; Productivity, price, means of production and land area are factors that affect the income level of farmers. Second; The average income level of corn farmers is low. The research results obtained are: (1) Based on the F test the productivity factors, selling price, production facilities, land area, together have a significant effect on the income level of corn farmers. Meanwhile, from the t-test it is known that productivity, production facilities, land area, each have a significant effect on the level of income of corn farmers and make a positive contribution. While the selling price has no significant effect but has a positive effect on the income level of corn farmers. (2) The average income level per respondent.